Groundwater for aDvancing Resilience (G4DR) in Africa - International Water Management Institute (International Water Management Institute, 2025)
The Groundwater for aDvancing Resilience (G4DR) in Africa project aims to support African countries in using groundwater more sustainably to improve water security and climate resilience. Funded by the Global Environment Facility (GEF) and implemented by the Food and Agriculture Organization of the United Nations (FAO), the project is executed by the International Water Management Institute (IWMI) in partnership with key partners, namely, African Ministers’ Council on Water (AMCOW), International Institute for Applied Systems Analysis (IIASA), Southern African Development Community – Groundwater Management Institute (SADC-GMI), and the national water ministries in Benin, Malawi, Mozambique, Togo, and Uganda. The project has three pilot sites - Shire Aquifer (Malawi and Mozambique), Upper Nile Water Management Zone (Uganda), and Mono River Basin (Benin and Togo), which will be areas to showcase practical solutions on groundwater management, monitoring and governance; contributing to the broader outcomes of the project, which include the integration of groundwater into national and regional planning, strengthening basin-level data and governance, enhancing capacity and facilitating stronger inclusion of women and youth in decision-making.